IMPACT OF SERVICE QUALITY ON REVISIT INTENTION AND WORD-OF-MOUTH INTENTION OF SUPERMARKETS THROUGH PRICE FAIRNESS, PERCEIVED VALUE AND SATISFACTION - Gilang Pratama Hafidz; Quartus Dominicius (Jurnal Ekonomi, 2023)
Retail is the last link in the goods distribution process. Through retail, products can meet directly with consumers. The purpose of this study is to prove the effect on revisit intention and WOM intention for supermarkets. Further factors can be seen in the variable service quality, price fairness, perceived value and satisfaction. This is a quantitative study using a purposive sampling technique distributed through questionnaires to 240 supermarket visitor respondents aged at least 17 years, have visited the supermarket at least 2x and are domiciled in JABODETABEK. The analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that service quality has the most impact on price fairness and perceived value. For the indirect effect, satisfaction mediates the relationship between service quality with revisit intention and WOM intention. This study provides suggestions for supermarkets to focus on service quality and perceived value to increase satisfaction so that customers have visit intention and WOM intention. The researcher suggests for further research to increase the number of respondents and make the proportion of respondents' ages more even.